THE VARIATION OF THE NOS3 GENE RS1799983 IS NOT ASSOCIATED WITH PREECLAMPSIA IN MALAY POPULATION - Citra Maharani; Herlambang Herlambang; Anggelia Puspasari (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2022)
ABSTRACT Background: eNOS play role in preeclampsia pathophysiology due to disturbing spiral arteries re-modelling and enhanced maternal vasoconstriction. A genetic variant of NOS3 associated with eNOS level. In addition, the previous study reported a genetic variant of NOS3 rs1799983 as a risk of preeclampsia with conflicting results beyond the population. To the best of our literature search, this genetic variant as preeclampsia risk has never been reported in the Jambi Malay population. This study aims to determine the association of the NOS3 genetic variant with preeclampsia in the Jambi Malay population. Methods: This study was a cross-sectional study that involved 43 pregnant women suffering preeclampsia and 53 normotensive pregnant women. All the subject resides in Jambi Province and was Jambi Malays. Genotyping was performed with tetra ARMS-PCR. Bivariate statistically analysis was performed. Result: The frequency of GT genotype was lower in the preeclamptic group and GG genotype was higher in the preeclamptic group than the TT genotype, but the difference was not statistically different for NOS3 rs1799983. Conclusion: Our findings indicate that the genetic variant of NOS3 rs1799983 is not associated with preeclampsia in the Jambi Malay population. Keywords: NOS3, eNOS, rs1799983, genetic variant, preeclampsia, Malay population ABSTRAK Pendahuluan: eNOS berperan dalam patofisiologi preeklamsia karena mengganggu remodelling arteri spiralis dan meningkatkan vasokonstriksi maternal. Varian gen NOS3 berkaitan engan peningkatan kadar eNOS. Penelitian sebelumnya melaporkan hasil yang bertentangan pada berbagai populasi terkait hubungan antara varian gen NOS3 rs1799983 dengan risiko kejadian preeklamsia. Sejauh pencarian literatur, varian gen NOS3 rs1799983 sebagai risiko preeklamsia belum pernah dilaporkan pada populasi Melayu Jambi. Penelitian ini bertujuan mengetahui hubungan varian gen NOS3 dengan preeklamsia pada populasi Melayu Jambi. Metode: Penelitian ini menggunakan desain potong lintang, melibatkan 43 orang ibu hamil dengan preeklamsia dan 53 orang ibu hamil normotensif. Semua subjek berdomisili di Provinsi Jambi dan merupakan orang Melayu Jambi. Pemeriksaan genotip dilakukan dengan metode tetra ARMS-PCR. Analisis statistik dilakukan meggunakan uji bivariat. Hasil: Hasil analisis didapatkan frekuensi genotip GT lebih rendah pada kelompok preeklampsia dan genotip GG lebih tinggi pada kelompok preeklampsia dibandingkan genotip TT, namun perbedaan tersebut tidak berbeda bermakna secara statistik. Kesimpulan: Hasil penelitian ini mengesankan bahwa varian genetik NOS3 rs1799983 tidak meningkatkan risiko preeklampsia pada populasi Melayu Jambi. Kata kunci: NOS3, eNOS, rs1799983, varian genetik, preeklamsia, populasi Melayu